The Use of START/STOPP Criteria for Elderly Patients in Primary Care - Muhteşem Erol Yayla; Uğur Bilge; Elif Binen; Ahmet Keskin (The Scientific World Journal)
Aim. Our aim was to detect older patients who were prescribed inappropriate drugs according to START/STOPP criteria in primary care. Materials and Method. Patients aged over 65, admitted to health center no. 5 in Afyon, were included. The files of the subjects were surveyed retrospectively for the final one year in the digital environment, using the Family Medicine Information System. The files surveyed allowed us to list the drugs they used in the past year and to detect inappropriate drug use. Results. The number of patients that took part in this study was 325 (average age: years). We found that, among these participants, 48 patients (14.8%) were using drugs inappropriately according to STOPP criteria. Conclusion. Further focus on avoiding inappropriate drug use will allow clinicians and other health professionals to reduce side effects and other complications. In patients aged over 65, there is a need to attach particular importance to inappropriate drug use, drug interactions, and avoidance of side effects.